An approach to the impact of weather variables on the growth of Polylepis species in the central Andes of Peru - Ortega Quispe, Kevin Abner (2025)
The Polylepis genus, endemic to the South American Andes, faces significant threats due to environmental variations, which jeopardize its growth and survival. This situation underscores the urgent need to develop conservation strategies. The present research assesses the influence of meteorological variables, such as temperature and humidity, on the growth and adaptation of various Polylepis species in the central Peruvian Andes, aiming to optimize reforestation and sustainable management practices. The study was conducted in experimental plots at the Santa Ana Agricultural Station in Junín, Peru, where Polylepis saplings, obtained from different localities, were planted. Over two years, phenotypic variables (height and diameter) and meteorological variables (precipitation, humidity, temperature, and wind speed) were monitored to evaluate the relationship between environmental conditions and plant development. The results showed that high humidity negatively affected all species, however wind speed appears to promote plant growth by creating an ideal microclimate that reduces soil moisture. Precipitation and maximum temperature had limited impact, indicating relative resilience to these factors. It should be noted that the species from Huancavelica and Yauyos have been adapting better to local conditions compared to those from Cerro de Pasco, which are more sensitive to humidity. These findings highlight the importance of considering wind speed and humidity in reforestation planning to improve the adaptability of Polylepis species. We conclude that humidity is the most decisive meteorological factor for the growth of Polylepis under specific conditions, emphasizing its relevance in planning conservation and reforestation strategies in the Peruvian Andes.